Cercopithecine Herpesvirus 9 (Simian Varicella Virus) Infection after Total-Body Irradiation in a Rhesus Macaque (Macaca mulatta) - Gulani, Jatinder (Comp Med, 2016)
This case report describes a rhesus macaque (Macaca mulatta; male; age, 5 y; weight, 6.7 kg) with anorexia, dehydration, lethargy, ataxia, and generalized skin rashes that occurred 30 d after total-body irradiation at 6.5 Gy ((60)Co γ-rays). Physical examination revealed pale mucus membranes, a capillary refill time of 4 s, heart rate of 180 bpm. and respirations at 50 breaths per minute. Diffuse multifocal maculopapulovesicular rashes were present on the body, including mucocutaneous junctions. The CBC analysis revealed a Hct of 48%, RBC count of 6.2 × 10(6)/µL, platelet count of 44 × 10(3)/µL, and WBC count of 25 × 10(3)/µL of WBC. The macaque was euthanized in light of a grave prognosis. Gross examination revealed white foci on the liver, multifocal generalized petechiation on serosal and mucosal surfaces of the gastrointestinal tract, hemorrhagic lymph nodes, and hemorrhagic fluid in the thoracic cavity. Microscopic examination revealed cutaneous vesicular lesions with intranuclear eosinophilic viral inclusions within the epithelial cells, consistent with herpesvirus. Immunohistochemistry was positive for herpesvirus. The serum sample was negative for antibodies against Macacine herpesvirus 1 and Cercopithecine herpesvirus 9 (simian varicella virus, SVV). Samples submitted for PCR-based identification of the etiologic agent confirmed the presence of SVV DNA. PCR analysis, immunohistochemistry, and histology confirmed that lesions were attributed to an active SVV infection in this macaque. This case illustrates the importance of screening for SVV in rhesus macaques, especially those used in studies that involve immunosuppressive procedures.